COMMUNITY ACQUIRED PNEUMOCOCCAL PNEUMONIA IN NORTHWESTERN NIGERIA: EPIDEMIOLOGY, ANTIMICROBIAL RESISTANCE AND OUTCOME - Iliyasu, Garba; Mohammad, Farouq Dayyab; Habib, Abdulrazaq Garba (African Journal of Infectious Diseases (AJID), 2017)
Background: Pneumococcus is the leading cause of community acquired pneumonia (CAP) worldwide, and the leading cause of mortality. Pneumococcal pneumonia is poorly studied in Nigeria. We describe the epidemiology including associated co-morbidities and outcome of pneumococcal pneumonia in North-western Nigeria. Material and methods: We conducted a prospective, hospital based study on patients with community acquired pneumococcal pneumonia. Detailed clinical evaluation and relevant laboratory investigations were carried out. Susceptibility test to commonly used antibiotics was carried out on all confirmed pneumococcal isolates. In hospital mortality was recorded. Analysis was carried out using descriptive statistics with differences and relationships were determined using Chi square and Fisher’s exact tests as appropriate, with p < 0.05 regarded as significant. Results: Of the one hundred and twenty-five (125) patients with pneumococcal pneumonia were studied. The mean age of the patients was 41.3years (± 16.84), and 69/125(55.2%) were males. Co-morbidities were observed in 63/125 (53.8%) of the patients. Resistance to commonly used antibiotics was observed. Overall in-hospital mortality was 9/117(7.8%). HIV (OR=2.081; 95%CI 1.651-3.237), age ≥65years (OR=5.947; 95%CI3.581-17.643), and CURB-65 score of ≥ 3 (OR=2.317; 95%CI1.734-4.719) were independent predictors of mortality. Conclusion: Pneumococcal pneumonia is the commonest cause of CAP in North-western Nigeria with relatively high mortality. There is need to strengthened the vaccination policy targeting at risk adult population in Nigeria.